Changes in in-plane electrical conductivity of PEDOT:PSS thin films due to electric field induced dipolar reorientation. Issue 105 (13th October 2015) - Mahajan, Mrunal S.; Marathe, D. M.; Ghosh, Sanjay S.; Ganesan, V.; Sali, Jaydeep V.
Abstract : A model, based on induced reorientation of PEDOT:PSS chains due to electric field interaction with electric dipoles of the chains, has been proposed to explain observed resistivity switching and anisotropic in-plane conductivity in PEDOT:PSS films. Abstract : Orientation of polar polymer chains can be achieved by direct application of high electric field to the polymer thin films. Changes in morphology due to such electric field treatment can impart changes in electrical conductivity of the thin films. PEDOT:PSS thin films exhibit isotropic in-plane electrical conductivity. We have observed that the electric field treatment at high temperature lead to anisotropic behaviour in in-plane conductivity of thin film of PEDOT:PSS film. In case of films prepared with aqueous solution of PEDOT:PSS, electric field treatment cause rise in electrical in-plane conductivity in orthogonal direction to electric field and it falls in direction of electric field. Thin films prepared with DMSO added aqueous solution of PEDOT:PSS show initial isotropic switching from high conductivity to low conductivity state due to electric field treatment. Prolonged treatment resulted in significant fall in in-plane electrical conductivity specifically in the direction of electric field. A model, based on re-orientation of polymer chains caused by interaction of electric field and electric dipoles of PEDOT:PSS chains, has been proposed to explain this behaviour. The hypothesis is supported by the results of Raman spectroscopy. Co-relating changes are also recorded in absorption spectra of these films. This study may find application in write once read many memory devices based on PEDOT:PSS.